PENGARUH NET PROFIT MARGIN, TOTAL ASSET TURNOVER, PRICE TO EARNING RATIO, DAN SALES GROWTH TERHADAP RETURN SAHAM (Studi pada Perusahaan Sektor Healthcare yang Terdaftar di Bursa Efek Indonesia Periode 2019-2024) - Widiya Maulida; Rizki Pratomo Sunarwibowo (Nirta Learning Centre, 2026)
This study aims to analyze the effect of net profit margin, total asset turnover, price to earning ratio, and sales growth on stock returns of healthcare sector companies listed on the Indonesia Stock Exchange during the 2019-2024 period. The study employs a quantitative approach with a causal associative research design, using a sample of 16 companies selected through purposive sampling. The data consist of secondary data derived from statements of financial position, profit and loss statements, dividend data, and closing stock prices, which are analyzed using panel data regression with a Fixed Model approach through Stata 17 software. The results indicate that total asset turnover and price to earning ratio have a positive effect on stock return, while net profit margin and sales growth have no effect on stock returns. These findings suggest that asset utilization efficiency and market expectations regarding firm value are more strongly considered by investors that profitability levels and sales growth in determining stock returns in the healthcare sector. Therefore this study is expected to contribute to investors investment decision making and serve as a reference for future research.